Pengendalian Penyakit Hawar Daun Phytophthora pada Bibit Kakao dengan Trichoderma asperellum - Asti Irawanti Azis; Ade Rosmana; Vien Sartika Dewi (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Phytophthora leaf blight caused by Phytophthora palmivora is one constraint in cacao seedling in Indonesia. Generally, synthetic fungicides were applied to control this disease but its negative impact is becoming obvious recently. Research was conducted to evaluate the effectiveness of two Trichoderma asperellum isolates, ARBT-1 and ART-4, to suppress disease development. The two isolates were applied through seed treatment with spore concentrations of 104 mL-1, 105 mL-1, and 106 mL-1. The results showed that disease incidence on seedling treated with different spore concentrations of ARBT-1 was 39.0%, 23.6%, and 21.8%, respectively and those with ART-4 was 30.6%, 25.7%, and 30.8%, respectively, whereas disease incidence reached 90.3% for control at 21 days after inoculation of the pathogen. Observations on cocoa leaf tissues showed that the two isolates were found in leaf tissue, indicating that T. asperellum is an endophyte.Key words: antagonistic fungi, seedling, seed treatment